Utilization of vinasse for the production of polyhydroxybutyrate by Haloarcula marismortui - Pramanik, Arnab; Mitra, Anindita; Arumugam, Meyyappan; Bhattacharyya, Anirban; Sadhukhan, Sohini; Ray, Atrayee; Haldar, Saubhik; Mukhopadhyay, Ujjal Kumar; Mukherjee, Joydeep (Folia microbiologica, 2012)
Vinasse, a recalcitrant waste of the ethanol industry was employed for the production of polyhydroxyalkanoate (PHA) by the extremely halophilic archaeon, Haloarcula marismortui in shake flasks. The PHA was recovered by osmotic lysis of the cells and subsequent purification by sodium hypochlorite and organic solvents. Through UV-vis spectroscopy, differential scanning calorimetry, Fourier transform infrared, and nuclear magnetic resonance spectroscopy, the PHA was found to have characteristics very similar to that of the standard polyhydroxybutyrate (PHB) from Sigma. Inhibitory effect of polyphenols contained in vinasse was assessed by a quick and reliable cup-plate agar-diffusion method. Raw vinasse (10%) was utilized leading to accumulation of 23% PHA (of cell dry weight) and following an efficacious pre-treatment process through adsorption on activated carbon, 100% pre-treated vinasse could be utilized leading to 30% accumulation of PHB by H. marismortui. Maximum specific growth rate, specific production rate, and volumetric productivity attained using 10% raw vinasse were comparable to that obtained using a previously reported nutrient deficient medium (NDM), while the values with 100% pre-treated vinasse were higher than that determined using NDM medium. This is the first report of polyhydroxybutyrate production by a halophilic microorganism utilizing vinasse.
Keywords: Archaeal Proteins; Gene Expression Regulation, Archaeal; Refuse Disposal; odpadky - odstraňování; Industrial Waste; Haloarcula marismortui; polyhydroxyalkanoáty; archeální proteiny; Polyhydroxyalkanoates; regulace genové exprese u archeí; průmyslový odpad